ANALISIS POTENSI AGROWISATADI KABUPATEN KARO - Apprila Natasya Br Surbakti; Isnaini Harahap; Annio Indah Lestari (Studia Economica : Jurnal Ekonomi Islam, 2021)
The potential of Agrotourism in Karo Regency is very well developed for the future. Tourism visiting Karo Regency from year to year continues to increase because Karo Regency is a Regency known for its types of plants and tourism. The geographical area which is located in a mountainous/highland area makes Karo Regency has the potential to become a tourism destination. The coolness of nature is an aspect that triggers tourist interest to visit tourist areas in Karo Regency. The tourism targets in Karo Regency are natural tourism objects, cultural tourism, historical heritage, agro-tourism, and playgrounds. This research aims to identify the potential for developing agro-tourism in Karo District and identify strategies regarding efforts to develop agro-tourism in Karo District. This research uses a descriptive qualitative approach and SWOT analysis. Based on the results of the internal analysis of Agrotourism in Karo Regency, there are three strengths including strategic location, having a beautiful panorama and the community giving a good response to Agrotourism in Karo Regency. The weakness is the lack of technology that is still used in Agrotourism in Karo Regency itself is still simple or traditional, there are limitations on facilities and facilities in Agrotourism gardens in Karo Regency, and promotions that have not been aggressive and intensive. Based on the results of the external environment of Agrotourism in Karo Regency, opportunities are obtained, namely technology that is growing, the number of visitors during the holiday period is increasing, people's lifestyles (back tone). The results of the SWOT analysis of Agrotourism Potential in Karo Regency that the results in the IFAS and EFAS Matrix tables of Agrotourism Potential in Karo Regency are in cell I, namely the situation where Agrotourism in Karo Regency is located in Growth, namely Concentration on Vertical Integration, namely the strategy of using Backward integration (shifting the role of suppliers) ) or Forward Integration (switching the role of distributor).